2020
DOI: 10.2337/db20-0384
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 Dissociates Adipose Tissue Inflammation From Insulin Sensitivity in Obesity

Abstract: Obesity fosters low-grade inflammation in white adipose tissue (WAT) that may contribute to the insulin resistance that characterizes type 2 diabetes. However, the causal relationship of these events remains unclear. The established dominance of STAT1 function in the immune response suggests an obligate link between inflammation and the comorbidities of obesity. To this end, we sought to determine how STAT1 activity in white adipocytes affects insulin sensitivity. STAT1 expression in WAT inversely correlated w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 52 publications
1
21
0
1
Order By: Relevance
“…8 ). These observations add to the growing number of reports invoking a potentially dichotomous relationship presented by inflammation in obesity: (a) the potentially advantageous inflammatory contributors to obesity development 15 , 32 , 48 and (b) established obesity-driven inflammatory cytokines that can exacerbate downstream metabolic derangements 49 . Thus, a balance between these two functions of the immune system likely needs to be tightly controlled and regulated.…”
Section: Discussionmentioning
confidence: 69%
“…8 ). These observations add to the growing number of reports invoking a potentially dichotomous relationship presented by inflammation in obesity: (a) the potentially advantageous inflammatory contributors to obesity development 15 , 32 , 48 and (b) established obesity-driven inflammatory cytokines that can exacerbate downstream metabolic derangements 49 . Thus, a balance between these two functions of the immune system likely needs to be tightly controlled and regulated.…”
Section: Discussionmentioning
confidence: 69%
“…STAT1 has been related to prognosis of early-stage colorectal cancer [ 450 ], as constitutively active STAT is a hallmark of many cancers, also correlating inversely with FBG levels in obese humans and mice [ 451 ]. Also other inflammatory diseases, especially IBD, have been related to STAT3 activation [ 452 ].…”
Section: Markers Of Inflammation Relation To Disease and Practicamentioning
confidence: 99%
“…Recently, it was reported that miR-155-5p directly regulated Gsk3b and participated in the regulation of steroid metabolism (39), and that Nr1h3 was related to autophagy. STAT1 was reported to be related to inflammation and insulin sensitivity in adipose tissue and obesity (40). MAPK14 has a wide effect on regulating inflammation and metabolism, and was shown to be regulated by miRNA epigenetics in PCOS in our previous study (24).…”
Section: Discussionmentioning
confidence: 83%